Upaya Pembentukan Brand Awareness di Dalam Negeri oleh Triple S - Roidisom, Shamit; Hafiar, Hanny; Novianti, Evi (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
PT Triple S is known as sport kit factory in Indonesia, and specialist of soccer ball. PT Triple S has a good product, however the brand itself acknowledged internationally better than domestically. Brand awareness is built through marketing communication. Therefore, this case study inquiry is trying to identify the technique of creating brand awareness with marketing communication strategy by PT Sinjaraga Santika Sport (Triple S) in Indonesia. The goal of this research is to have knowledge of creating brand awareness technique using marketing communication by PT Sinjaraga Santika Sport (Triple S). This study is utilizing qualitative approach, constructivism paradigm and case study as form of study. The Subject were people who is implicated by brand awareness strategy of PT Triple S,  for instance employees and customer of  PT Triple S.The results of this research gave out that marketing communication is being done by PT Triple S in order to create brand awareness in Indonesia. But, the inhibition both internal obstacle (from the company itself) for example uncertainty of human resources’s skill on executing marketing communication strategy and external obstacle (Indonesian consumer stereotype that think import products are better than local product) has created the fact that brand of Triple S is acknowledged better internationally than domestically. As for the closure of this research: marketing communication strategies that successfully creates brand awareness internationally are their ball officially certified by FIFA, they also had an agreement and entered World Cup 1998. Meaanwhile marketing communication is also being donein Indonesia but the obstacles both internal and external  has caused a misfortune for PT Triple S in order to create brand awareness domestically.